Strength Stability of Aging Hardened Mg-10Y-1.5Sm Alloy. Issue 3 (March 2018) - Qing, Zhang; Jun, Chen; Quanan, Li
Abstract : Abstract: The tensile strength stability of aging hardened Mg-10Y-1.5Sm (mass fraction, %) alloy was investigated by microstructure analysis and tensile tests. The results show that the microstructure of Mg-10Y-1.5Sm alloy consists of α -Mg matrix and Mg24 Y5 phase and the formation of Sm-containing phase is not observed. With the increase of temperature from 20 to 300 o C, the tensile strength exceeds 200 MPa and has no obvious change. It is insensitive to temperature and the variation range is less than 10 MPa. The strength stability is superior to that of heat resistant magnesium alloy WE54 developed most successfully. It is mainly attributed to the hardness stability of strengthening phase Mg24 Y5 enhanced by dissolved Sm.